2008
DOI: 10.1021/ac8022444
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Analytical Methodology Combining Micro-X-Ray Diffraction, Scanning Electron Microscopy-Based Mineral Maps, and Diffuse Reflectance Infrared Fourier Transform Spectroscopy to Characterize Archeological Artifacts

Abstract: Excavations at the 14th century Moorish rampart (Granada, Spain) unearthed a brick oven alongside black ash and bone stratigraphic layers. In situ evidence suggests the oven served to fabricate a wall coating including powdered burnt bones. Original ad hoc analyses improved on conventional methods were used to confirm this hypothesis. These methods enable (i) nondestructive micro-X-ray diffraction (mu-XRD) for fast mineralogical data acquisition (approximately 10 s) and moderately high spatial (approximately 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…The leaching of sodium ions in the cycles 1, 2, and 3 were ∼32.75, ∼29.87, and ∼26.51% (w/w) whereas the compound Na 2 O (Na 2 CO 3 , NaHCO 3 and H 2 CO 3 ) was ∼40.82, ∼43.52, and ∼33.31, respectively. [22]. This may be due to chemisorbed CO 2 in fresh RM and NRM respectively.…”
Section: Micro-morphological Characterization By Sem and Change Of Chmentioning
confidence: 98%
“…The leaching of sodium ions in the cycles 1, 2, and 3 were ∼32.75, ∼29.87, and ∼26.51% (w/w) whereas the compound Na 2 O (Na 2 CO 3 , NaHCO 3 and H 2 CO 3 ) was ∼40.82, ∼43.52, and ∼33.31, respectively. [22]. This may be due to chemisorbed CO 2 in fresh RM and NRM respectively.…”
Section: Micro-morphological Characterization By Sem and Change Of Chmentioning
confidence: 98%
“…Here the change in the dipole moment of the water hydroxyl-stretching plays an important role and so the intensity of the infrared spectrum is more. Stretching vibrations of C=O is found at 1449.40 cm -1 confirms the presence of carbonate groups [14]. …”
Section: Ft-ir Analysismentioning
confidence: 70%
“…It revealed that the peaks of gibbsite in NRM were increased prominently and a new mineral ilmenite (FeTiO 3 ) was formed, due to CO 2 treatment. But, after thermal treatment of [23][24][25]. This may be due to chemisorbed CO 2 in RM and NRM, respectively.…”
Section: Characterization Of Adsorbentmentioning
confidence: 99%